Overview of Family Knowledge Level and Support Regarding Diet in Diabetes Mellitus Patient - Dewi Astuti; Sukmana, Mayusef; Ahmad Abdul Ghofar Abdulloh; Sholichin (Fakultas Kedokteran, Universitas Mulawarman, 2025)
Background: Lack of family understanding about the diabetes mellitus diet affects the support given to patients. Knowledge about diet and family support provided to diabetes mellitus patients is one of the main assets for patients to remain actively involved in the implementation of the diabetes mellitus diet. Purpose: This study aims to describe the level of family knowledge and support regarding diet in diabetes mellitus patients at Loa Janan Public Health Center. Method: This research design is descriptive with a quantitative approach. A total of 30 respondents were selected using purposive sampling based on the inclusion criteria of families who have lived together for at least six months and reside in the working area of Loa Janan Public Health Center. Results: The study results on family knowledge and support regarding diet in diabetes mellitus patients at Loa Janan Public Health Center indicate a low level of knowledge among 14 respondents (47%) and good family support among 23 respondents (77%). Conclusions: The level of family knowledge falls into the low category, whereas family support is classified as good in diabetes mellitus patients. It is hoped that the findings of this study can help improve knowledge about diet.